2016
DOI: 10.1002/jclp.22369
|View full text |Cite
|
Sign up to set email alerts
|

Maternal PTSD and Children's Adjustment: Parenting Stress and Emotional Availability as Proposed Mediators

Abstract: Results highlight the need to target parenting stress in interventions with trauma-exposed families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
43
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 70 publications
8
43
1
1
Order By: Relevance
“…This is particularly important given the bidirectional and interrelated nature of relationships between the spouse, service member, and children in the family system (Verdeli et al., ). Untreated maternal psychopathology, for example, is associated with worse child outcomes (Goodman et al., ; Samuelson, Wilson, Padrón, Lee, & Gavron, ) and, in our sample, half (49.96%) of all participants who screened positive for problematic drinking had children, and approximately two thirds of those who screened positive for PTSD, depression, and anxiety had children (67.85, 70.17, and 67.88%, respectively). Spouses may be more willing than service members to seek services for themselves and their families (Eaton et al., ), which may help redress the problem of low treatment utilization among symptomatic service members (Hoge et al., ).…”
Section: Discussionmentioning
confidence: 56%
“…This is particularly important given the bidirectional and interrelated nature of relationships between the spouse, service member, and children in the family system (Verdeli et al., ). Untreated maternal psychopathology, for example, is associated with worse child outcomes (Goodman et al., ; Samuelson, Wilson, Padrón, Lee, & Gavron, ) and, in our sample, half (49.96%) of all participants who screened positive for problematic drinking had children, and approximately two thirds of those who screened positive for PTSD, depression, and anxiety had children (67.85, 70.17, and 67.88%, respectively). Spouses may be more willing than service members to seek services for themselves and their families (Eaton et al., ), which may help redress the problem of low treatment utilization among symptomatic service members (Hoge et al., ).…”
Section: Discussionmentioning
confidence: 56%
“…Chronic PTSD could increase the risk of women's other mental and physical health problems but also could deteriorate social functioning and impact the nearby environment and the child. Some studies demonstrated that maternal PTSD may be associated with negative child behavior outcomes (externalizing, internalizing, and emotion regulation) [52,53]. This relation could be explained because parents' PTSD can impact the functioning of parenting (lower parenting satisfaction, less optimal parent-child relationships, and more frequent use of negative parenting practices, such as overt hostility and controlling behaviors [54]).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a good alliance with the therapist motivates caregivers to improve their parenting behavior, as taught in TF-CBT. This treatment component seems especially important in PTSS, as the difficulties mentioned above often challenge caregivers’ skills, leading to vicious circles of negative communication and behavior [ 54 ].…”
Section: Discussionmentioning
confidence: 99%